2010
DOI: 10.4103/0975-3583.70911
|View full text |Cite
|
Sign up to set email alerts
|

Association of metabolic syndrome with obesity measures, metabolic profiles, and intake of dietary fatty acids in people of Asian Indian origin

Abstract: Objective:The present community-based cross-sectional study was aimed to examine the association of metabolic syndrome (MS) with obesity measures, metabolic profiles, and intake of dietary fatty acids in Asian Indian population.Patients and Methods:A total of 350 adult (30 years and above) individuals (184 males and 166 females) inhabiting in and around Kolkata, India participated in this study. MS was defined using the protocol specifically designed for Asian Indian population.Results:The prevalence of MS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
(27 reference statements)
2
23
2
Order By: Relevance
“…The WHRs measured in our current study were 0.85 -0.08 for the total group, 0.89 -0.08 in men and 0.82 -0.06 in women, which are different from those of other reports: 0.90 -0.09 in men and 0.91 -0.10 in women in a population-based sample of 12,514 (Das et al, 2010). Our measurements are also lower than those reported for a Chinese cohort from the Plain of Shenyang (Yong Liu et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…The WHRs measured in our current study were 0.85 -0.08 for the total group, 0.89 -0.08 in men and 0.82 -0.06 in women, which are different from those of other reports: 0.90 -0.09 in men and 0.91 -0.10 in women in a population-based sample of 12,514 (Das et al, 2010). Our measurements are also lower than those reported for a Chinese cohort from the Plain of Shenyang (Yong Liu et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…The overall prevalence of Metabolic Syndrome was found to be 42.1% in this study with higher prevalence among women (62.3%) as compared to men (24.6% [19][20][21] reported lesser prevalence of Metabolic Syndrome among adults (ranging from 24.9 to 31.4%) probably because of lower age group (<60 years) of the study subjects. In our study, higher prevalence of Metabolic Syndrome among women aged sixty or more was probably due to hormonal changes after menopause.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies also reported similar findings. 11,[18][19][20][21]24,25,27,28 Probably, this is the first study conducted in India which analyzed the prevalence of Metabolic Syndrome and its probable risk factors among the geriatric population residing in old age home. Since this study was conducted with a small sample size, the findings can"t be generalized.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Total protein, total energy, total fat, total polyunsaturated fat (PUFA) and monounsaturated fat (MUFA) contents of various foods were obtained using the standard guidelines. [15] The standardization to convert foodstuffs into fatty acids has been mentioned elsewhere.…”
Section: Methodsmentioning
confidence: 99%